Peran Women’s International League For Peace And Freedom Dalam Pemberdayaan Perempuan Afghanistan - Adam, Muhamad Devasso Azzura; Nababan, Fani Agustina; Abror, Muhammad Yusuf; Yusa, Muchammad Yustian (Department of International Relations, Brawijaya University, 2022)
ABSTRACT Women's discrimination is always happening in Afghanistan caused by the frequent conflict that occurred in Afghanistan and also poverty. This issue of discrimination also received attention from the international organization both government or non-government. One of the non-governmental international organizations that participated in this issue are Women International League for Peace and Freedom (WILPF). This research aims to analyse the role of WILPF related to women's empowerment in Afghanistan. This research uses qualitative method and descriptive research to explain the role of WILPF to empower Afghan women. The concept of this research are international non-governmental organization (NGOs) and transnational feminism to explain the efforts to empower Afghan women by WILPF for peace mission. The finding of this research addresses that the role of WILPF in Afghanistan to empower Afghan women who is through education, advocacy, empowerment of individuals, and monitoring agreement. Keywords: Afghan Women, Discrimination, Empowerment, Feminism, WILPF